An Eco Critical Reading of Lohani’s ’Gaia’ and V.S. Rai’s ’Corona Says’ - Pokhrel, Chet Bahadur (Janapriya Journal of Interdisciplinary Studies, 2022)
Environment is the indispensable domain of human beings which provides the larger platform of various activities. Essentially, violation of environmental ethics has been the hue and cry at present. This paper aims to explore the environmental issues imbedded in the poems of Shreedhar Lohani’s Gaia and Vishnu Singh Rai’s Corona Says. The purpose of this research is to explore and highlight the anthropocentrism, man-nature relationship and the consequences of the transgression of nature. This qualitative research investigates the select poems ‘Gaia’ and ‘Corona Says’ from an eco-critical approach. The qualitative method of interpretation is used to analyze both of the poems. The secondary data has been used to interpret the texts as they are published in the text books. An examination on these poems sheds lights on the idea that the random use of resources and human indifference to nature brings immeasurable consequences to human beings. The study concludes that the poems are thematically interconnected, rich in eco critical awareness and reaffirm that the excessive practice of any ideology either eco centrism or anthropocentrism has adverse effects on environment. From the study, it is deduced that green ecology and the ecological balance should be the new human agenda in the 21st century.